SISTEM INFORMASI PENGOLAHAN DATA INVENTARIS DAN PENGDAAN BARANG PADA KANTOR DESA LENTING BERBASIS WEB - Maulana Ashari; Juaini Juaini (Jurnal Manajemen Informatika dan Sistem Informasi, 2018)
Village Office Lenting currently conducting recording of inventory items with System manual partly done by making the recording by using a paper filing, which can lead to errors that are caused by humans, so that the data processing inventory of goods less effective to generate an inventory report items quickly and accurately. System development method that I use is the system Rapid Appliction Development (RAD). In the current system portion of the process is still done manually as recording inventory inventory still use hand writing and making of the report is still not effective because it must be noted back stock inventory items that have been used so that it can lead to errors that cause the information obtained is less accurate and effective. In the implementation, application inventory of these items can reduce errors - errors that occur when recording the inventory, transactions demand for goods, and also can provide information that is accurate and can be used as a foundation for the leadership of government agencies, in making decisions for the benefit of government agencies in the future.